The lost generation: Effects of youth labor market opportunities on long-term labor market outcomes - Venke Furre Haaland (Statistics Norway, Research Department, 2016)
Utilizing registry data for all Norwegian males born in 1959-1973, I demonstrate that local unemployment rates at the typical age of graduation from compulsory school (age 16) and highschool (age 19) have persistent, negative effects on males' earnings, employment, and disability pension utilization when measured as late as age 35. With data on every male IQ, I study how labor market conditions at age of graduation have differential effects for low- and high-ability males. As one would expect, low-ability males are particularly vulnerable to business cycles at the time of labor market entry.
Keywords: E32; J31; J24; 330; Business cycle; graduation; careers